2011
DOI: 10.1194/jlr.m019737
|View full text |Cite
|
Sign up to set email alerts
|

Lipid body formation during maturation of human mast cells

Abstract: This article is available online at http://www.jlr.org can be found in almost any type of cell ( 1 ). Currently, the role of lipid droplets in the pathophysiology of obesitydependent metabolic diseases involving insulin resistance is studied intensively ( 2 ). Lipid droplets are also present in various types of infl ammatory cells ( 3-6 ), where they are usually called lipid bodies (LB) and participate in cell signaling and in the generation of biologically active lipid mediators evoked by infl ammatory and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 39 publications
(28 reference statements)
3
37
0
Order By: Relevance
“…Interestingly, Dichlberger and colleagues have previously shown that a considerable amount of AA is found esterifi ed in the TG pool of human MCs ( 22 ). The current study now provides compelling evidence that ATGL releases AA from LD-associated TGs as a crucial step for eicosanoid biosynthesis in MCs.…”
supporting
confidence: 57%
“…Interestingly, Dichlberger and colleagues have previously shown that a considerable amount of AA is found esterifi ed in the TG pool of human MCs ( 22 ). The current study now provides compelling evidence that ATGL releases AA from LD-associated TGs as a crucial step for eicosanoid biosynthesis in MCs.…”
supporting
confidence: 57%
“…eicosanoids generated by oxygenation of the cPLA 2 α product free AA [78]. However, when added exogenously, the free fatty acid is able to induce significant LD formation in cells in the presence of cyclooxygenase and lipoxygenase inhibitors [39,40,52,54]. Importantly, this process occurs in a cPLA 2 α-dependent manner because blockade of the enzyme strongly inhibits LD formation [52,54].…”
Section: Pathways Leading To Cpla 2 α Activation That Impact On Ld Fomentioning
confidence: 96%
“…LDs of different cell populations such as eosinophils, macrophages, neutrophils or mast cell avidly incorporate exogenous AA. Lipid analyses of LDs isolated from blood leukocytes have shown that AA is mainly esterified in phospholipids [39], whereas in mast cells and macrophages it is found primarily in neutral lipids [40]. Whether these differences in localization have a physiological consequence or are due to other factors, i.e.…”
Section: Pla 2 and Lipid Dropletsmentioning
confidence: 98%
“…Surprisingly, the same effect was even more pronounced for the release of LTC4. Based on the current literature, ATGL is a single-compartmentacting enzyme that exerts its activity on TGs in LDs only, ( 9 ), these stores could serve as a quantitatively major source of AA for eicosanoid biosynthesis. In adipocytes under basal conditions, ATGL mediates the initial step in TG hydrolysis by producing 1,3-DAG, while under hormonal stimulation of lipolysis the enzyme becomes activated by its coactivating factor CGI-58, and the selectivity of ATGL broadens to the sn -1 position leading to the production of 2,3-DAG as well ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…MC LDs were visualized by Oil Red O staining and quantifi ed by fl ow cytometry as described previously ( 9 ). Briefl y, MCs were sedimented (Cytospin, Shandon Instruments) onto glass slides (15 × 10 3 cells/slide) and fi xed with 10% neutral buffered formalin solution (Sigma).…”
Section: Ld Visualization and Quantifi Cationmentioning
confidence: 99%